Pelatihan Bahasa Inggris untuk Layanan Wisata Berdasarkan Kebutuhan Lokal Bagi Pemilik Homestay di Kepulauan Raja Ampat Papua Barat - Purnomo, Budi (Proceeding SENDI_U, 2015)
The development of tourist visits to the Raja Ampat Islands of West Papua is so rapidly in thelast five years (2010-2015), but it is not supported by the readiness of local people to servetourists which leads local government thinks hard to find a solution. Because nearly 90% oftourists who come to Raja Ampat - one of the leading Indonesian archipelagoes maritimedestinations - are foreign tourists, the regional government decided to cooperate with tourismcolleges to train local people, especially their English language skills to serve foreign tourists.This study aims at answering a question: How to provide training of English for servingtourists based on local needs for homestay owners in the Raja Ampat Islands of West Papua?This case study is to answer the research question comprehensively about what, how and whythe subjects studied (Yin, 2009). The time of research was from September until December2014 located in Raja Ampat Islands with two English language teachers and 60 homestayowners representing four tribes in Raja Ampat, i.e. Usba, Sopen, Wardo and Amber asresearch subjects. The 1st stage study was based on local needs analysis approach and thenfollowed by action research on the 2nd stage. Needs of English language knowledge forhomestay owners were revealed in the 1st stage and then they were given training during the2nd stage with the material in the form of a conversation between homestay owners andtourists from tourist arrivals in the closest airport/port to the departure of tourists from thenearby airport/port. The data collection techniques include (1) observation and field notes, (2)questionnaires and (3) in-depth interviews. The techniques are the basis for the analysis usingtriangulation method. The research findings show that: (1) a suitable approach used in thetraining of English for serving tourists based on local needs for homestay owners in the RajaAmpat Islands of West Papua is by using teaching through relationships; (2) at an earlystage, the activity of learning is mostly done by imitating and repeating the same structurecontinuously; (3) the next learning stage is to remember dialogue. Learners were given shortdialogs and then asked to memorize expressions in the dialog, and then it ended by practices;and (4) after they were proficient with the conversations, they exchanged roles each other topractice the dialogs had been memorized. The results also imply that the training of Englishfor serving tourists is not only effective for improving English speaking skill for thehomestay owners in the Raja Ampat Islands, but also raises awareness of the importance ofservice quality to serve tourists in order improve the welfare of local people.Keywords: English for serving tourists, local needs, homestay owners